การประเมินผลการรักษาโรคลิ้นหัวใจไมตรัลตีบโดยวิธีการขยายด้วยบอลลูน ด้วยการตรวจคลื่นเสียงสะท้อนหัวใจขณะออกกำลังกายโดยการนอนถีบจักรยาน - ดิลก ภิยโยทัย (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
Objective : To evaluate the beneficial results of PTMC in decreasing mean mitral pressure gradient (MMPG) both at rest and during exercise and increasing mitral valve area (MVA). Method : Mitral stenosis (MS) patients planned for PTMC were included เท this study. Echocardiographie studies at rest and during exercise by supine ergometry were performed in all of them at 1 day before and 7 days after PTMC. Besides standard parameters, the measurements included MVA, MMPG and TRPPG (tricuspid regurgitant peak pressure gradient). Results : There were 22 patients (2 M and 20 F) with the mean age of 34 ± 16 years (mean ± 2SD). Mean MV score was 8.23 (range 6-10). MVA increased from 0.74±0.35 to 1.44±0.47 cm2 (p < 0.001). MMPG decreased from 12.03±9.17 to 5.49±4.24 mmHg at rest (p < 0.001) and from 24.30±13.93 to 14.72±8.64 mmHg during exercise (p < 0.001). TRPPG decreased from 51.20±37.42 to 33.62±28.46 mmHg at rest and from 97.40±34.35 to 73.54±42.12 mmHg during exercise (= 0.004). Conclusion : PTMC is an effective treatment for severe MS patients. lt can significantly increase MVA and decrease MMPG and TRPPG both at rest and during exercise. Supine ergometry is proved to be safe for evaluation MS patients after PTMC.